The Form Of "Fa’ala Yaf’ulu" and Its Meanings According to the Morphologists | ṣyghoh “Fa’ala Yaf’ulu” Wama’aniiha ‘Inda Aṣarfiiyn - Bello Muhammad; Awal Ibrahim Imam (Mantiqu Tayr: Journal of Arabic Language, 2022)
The open-eyed “Fa’ala” has several meanings, because it is the lightest and most frequently used weight in the Arabic language, and its lightness is what indicates its frequent use, and its meanings are more than other weights, and it conveys the meaning of plural, differentiation, giving, preventing, consenting, refraining, harming, prevailing, pushing, transferring, and stability. Walking, covering, stripping, throwing, reforming and corrupting, voting, order, appearance and nourishment.